2021
DOI: 10.1186/s12877-021-02344-1
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional relationship between subjective age and frailty: a prospective cohort study

Abstract: Background Subjective age refers to how young or old individuals experience themselves to be and is associated with health status, behavioral, cognitive, and biological processes that influence frailty. However, little research has examined the relationship between subjective age and frailty among older adults. This study examined the bidirectional association between subjective age and frailty among community-dwelling older adults. Methods We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…In previous studies, although there was no direct evidence, indirect evidence could prove that subjective age is associated with body balance and muscle endurance. For instance, Li et al [ 11 ], using a large sample of community-dwelling older people, found that adults with older subjective age than their chronological age were more likely to develop pre-frailty and frailty. It has been reported that body balance and muscle endurance, together with age and chronic diseases, are key risk factors for pre-frailty and frailty in the older population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, although there was no direct evidence, indirect evidence could prove that subjective age is associated with body balance and muscle endurance. For instance, Li et al [ 11 ], using a large sample of community-dwelling older people, found that adults with older subjective age than their chronological age were more likely to develop pre-frailty and frailty. It has been reported that body balance and muscle endurance, together with age and chronic diseases, are key risk factors for pre-frailty and frailty in the older population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that reduced cardiopulmonary endurance is related to an increased risk of developing functional decline and cognitive impairment in older people [ 34 , 35 , 36 ]. Functional decline and cognitive impairment have been reported to more or less be associated with subjective age [ 7 , 8 , 11 ]. This implies that there is a relationship between cardiopulmonary endurance and subjective age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjective age is an important predictor of positive health outcomes (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In a representative sample of 4,665 older community-dwelling people in Germany, the majority reported feeling younger than their chronological age.…”
Section: Discussionmentioning
confidence: 99%